Mobile health and neurocognitive domains evaluation through smartphones: A meta-analysis. (November 2021) - Siddi, Francesca; Amedume, Allen; Boaro, Alessandro; Shah, Aditi; Abunimer, Abdullah M.; Bain, Paul A.; Cellini, Jacqueline; Regestein, Quentin R.; Smith, Timothy R.; Mekary, Rania A.
Highlights: Mobile-Health applications are suitable to implement formal methods. Mobile applications correlate with validated neuropsychological assessments. Smartphones offer a cheaper and less invasive neurocognitive impairments' evaluation. The first meta-analysis in neurocognitive disorders' evaluation through smartphones. Abstract: Background: Mobile health (mHealth) have significantly advanced evaluating neurocognitive functions; but, few reports have documented whether they validate neurocognitive impairments as well as paper-and-pencil neuropsychological tests. Objective: To meta-analyze the correlation between mobile applications for neuropsychological tests and validated paper-and-pencil neuropsychological tests for evaluating neurocognitive impairments. Method: We used PubMed, Embase, Cochrane, Web of Science, and IEEE Explorer through January 2020 to identify studies that compared mobile applications for neuropsychological tests vs. paper-and-pencil neurophysiological tests. We used random-effects models via the DerSimonian and Laird method to extract pooled Pearson's correlation coefficients and we stratified by study design. Result: Nine out of 4639 screened articles (one RCT and eight prospective longitudinal case series) were included. For the observational studies, there was a statistically significant strong and direct correlation between mobile applications for neuropsychological test scores and validated paper-and-pencil neuropsychological assessment scores (r = 0.70; 95% CI 0.59, 0.79; I 2 = 74.5%; p- heterogeneity <0.001). Stronger results were seen for the RCT (r = 0.92; 95% CI 0.77, 0.97). Conclusion: This meta-analysis showed a statistically significant correlation between mobile applications and the validated paper-and-pencil neuropsychological assessments analyzed for the evaluation of neurocognitive impairments.